Electric vehicle propulsion system with fuzzy-logic-based DTC IPMSM drive. (22nd April 2008) - Jain, Pradeep; Singh, Bhim; Mittal, Alok Prakash; Gupta, Jai Ram Prakash
This paper deals with a fuzzy-logic-based direct torque control (DTC) of an interior permanent magnet synchronous motor (IPMSM) for electric vehicle (EV) propulsion systems. The DTC IPMSM drive has improved performance over the scalar- and vector-controlled drive, but it has high torque and stator current ripples. To overcome these problems the conventional switching lookup table of DTC is replaced with a fuzzy logic. The performance of DTC IPMSM with different EV features is compared for three-level and five-level torque control with and without fuzzy logic. The results, using Matlab, demonstrate the effectiveness of the DTC scheme of IPMSM drive using fuzzy logic.